The complex interactions between humans and the marine environment require new efforts to build beauty and harmony - Omstedt, Anders; Gustavsson, Bernt (Frontiers in Marine Science, 2022)
Human activities give rise to many factors exerting tremendous pressure on the ocean and its coastal seas. Simultaneously, social, political, and ecological environments are highly complex, with many competing interests. Marine system management and governance must therefore integrate many perspectives incorporating human perception and behavior. Here, we discuss how philosophy and science often address the investigation of reality. The starting points are the atomistic and holistic views and their interrelationships. The distinction between particular and universal claims is added to the atomistic and holistic views and broadened to encompass the context; perspectives on processes and system insights into coastal seas are then analyzed. We conclude that an atomistic view risks fragmenting our knowledge and treatment of nature and humans into many separate and conflicting compartments, while a holistic approach opens up the “whole” but at the risk of oversimplification. The distinction between particular and universal claims is essential, and universal human values are critical for reversing the decline in the marine environment. Adding an increasing number of processes to sea management initiatives could risk reducing public interest and increasing alienation from the sea. Atomistic and holistic, particular and universal, or processual and systemic understandings should not be treated as contradictory; instead, our understanding of reality can be transformed when these complementary perspectives meet.